Cosmetic Microdroplet Botulinum Toxin A Forehead Lift: A New Treatment Paradigm. Issue 4 (July 2015) - Steinsapir, Kenneth D.; Rootman, Daniel; Wulc, Allan; Hwang, Catherine
Abstract : Purpose: To investigate the safety and efficacy of a microdroplet, cosmetic, periocular botulinum toxin A method that extensively treats the eyebrow depressors but leaves the brow elevators untreated. Methods: This is a 5-year retrospective, consecutive, nonrandomized series of botulinum toxin treatments. The study was reviewed by an institutional review board and complied with the Health Insurance Portability and Accountability Act (HIPAA). Patients were treated with 33 U onabotulinum toxin (BOTOX, Allergan, Inc., Irvine, CA, U.S.A.) injected in microdroplets of 10 to 20 μl. Sixty to 100 injections of microdroplets were needed to complete a treatment pattern concentrated at the brow, glabella, and crows feet area. The forehead was not treated. Patients who returned between 10 and 45 days were studied with image analysis. Results: There were 563 consecutive microdroplet treatments on 227 unique patients (female, n = 175, mean age 46 ± 4 years; male, n = 52, mean age 44 ± 8 years). The incidence of ptosis was 0.2% and transient. Forty-nine patients returned for a follow-up visit between 10 and 45 days and were included for image analysis to compare the before and after results of treatment. The average brow height was 24.6 mm before and 25 mm after treatment ( p = 0.02). Photonumeric scales for forehead lines, brow ptosis, and brow furrow all showed statistically significant improvements ( p < 0.0001). Conclusions: The microdroplet brow lift method safely concentrates cosmetic botulinum toxin treatment along the eyebrow, crows feet, and glabellar area, resulting in a brow lift effect that reduces forehead lines, elevates the eyebrow, and reduces the furrow along the brow. This new treatment paradigm results in an aesthetic improvement to the face and periocular area without the forehead paralysis associated with conventional treatment. Abstract : The microdroplet method of cosmetic botulinum toxin A along the eyebrow and crow's feet area allows for a forehead lift and brow shaping without forehead paralysis and minimal risk of upper eyelid ptosis.